Evaluation of sixth grade primary schoolchildren's knowledge about avulsion and dental reimplantation - Castilho, Lithiene Ribeiro [UNESP]; Marcal Mazza Sundefeld, Maria Lucia [UNESP]; de Andrade, Dalton Francisco; Barioni, Sônia Regina Panzarini [UNESP]; Poi, Wilson Roberto [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Dental trauma, particularly tooth avulsion, is a frequent cause of tooth loss in children, adolescents, and young adults. The avulsed tooth should be immediately reimplanted in its alveolus. This procedure can be performed by anyone at the accident site and not only by dental surgeons. Therefore, the purpose of this study is to evaluate the knowledge of sixth graders of the city of Aracatuba, SP, about dental avulsion and tooth reimplantation through a structured and standardized survey. Our sample consisted of 778 students. The data collected was processed using the program epiinfo 2000. Most students were around 12 years of age and 94.5% related to practice some kind of sports. Results demonstrated that the possibility of tooth reimplantation after dental avulsion is not acknowledged among these students and dental traumatism was associated to caries, toothache, and use of orthodontic appliances. Only 18.9% of the students associated dental traumatism to an impact trauma; 3.6% would store the tooth in milk, and 3.1% believed the tooth could be reimplanted by anyone present at the accident site. In summary, the results show an overall the lack of knowledge about dental traumatism and highlight the need of special programs designed to educate school-aged students about emergency procedures to handle cases of dental traumatisms.